Intergenerational altruism: A solution to the climate problem? - Frikk Nesje; Geir B. Asheim (University of Oslo, Department of Economics, 2016)
The future effects of climate change may induce increased intergenerational altruism. But will increased intergenerational altruism reduce the threat of climate change? In this chapter we investigate this question. In a second-best setting with insufficient control of greenhouse gas emissions in the atmosphere, increased transfers to future generations through accumulation of capital might result in additional accumulation of greenhouse gases, and thereby aggravate the climate problem. In contrast, transfers to the future through control of greenhouse gas emissions will alleviate the climate problem. Whether increased intergenerational altruism is a means for achieving accumulation of consumption potential (through accumulation of capital) without increasing the climate threat depends on how it affects factors motivating the accumulation of capital and the control of emissions of greenhouse gases. An argument is provided for why increased intergenerational altruism in fact will aggravate the climate problem. We use the models of Jouvet et al. (2000), Karp (forthcoming) and Asheim and Nesje (forthcoming) to facilitate the discussion.
Keywords: D63; D64; Q01; Q54; 330; intergenerational altruism; climate change